ANALISIS KOMPARATIF KINERJA KEUANGAN PERBANKAN ASEAN SETELAH KRISIS GLOBAL - I Gusti Ayu Purnamawati (University of Merdeka Malang, 2014)
The globalization of world trade era presented a competitive challenge for the banking sector, especially thecountries that were members of the Association of Southeast Asian Nations (ASEAN) such as: Indonesia,Thailand, and Malaysia. The banking sector was very vulnerable to the economic turmoil that often occurred.The uncertainty in the global economic recovery resulted a high risk in the financial sector for the importanceof the banks financial performance assessment for the stakeholders. This study aimed to compare the financialperformance of the banking sector in Indonesia, Thailand, and Malaysia by using financial ratios. The samplewas limited to banks that fell into the category of 5 largest banks in Indonesia, Thailand, and Malaysia during2009-2012. The research data was secondary data obtained from the Indonesia Stock Exchange. The analysismethod used was Kolmogorov Smirnov test for data normality test and one-way ANOVA parametric test. Theresults showed that: (1) There were significant differences of indicators ROA, ROE and LDR in the financialperformance of banks in Indonesia, Thailand and Malaysia; (2) There was no difference of CAR indicator inbanking finance in Indonesia, Thailand and Malaysia.